2007
DOI: 10.1007/s10573-007-0077-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the degree of dispersion on the detonation wave structure in pressed TNETB

Abstract: A VISAR interferometer was used to study the reaction zone in steady-state detonation waves in pressed TNETB at different initial densities (1.23-1.71 g/cm 3 ) and degrees of dispersion (5 and 80 µm) of the initial powdered high explosive (HE). The initial density range in which a pressure rise was observed instead of the theoretically predicted chemical spike is shown to depend on the degree of dispersion of the HE. The unusual change in the parameters in the reaction zone is explained by the heterogeneous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
3
2
0
Order By: Relevance
“…Unfortunately, at low densities, fluctuations complicate the laser interferometry at the interface [12]. The method [15] using thick foils which provide averaging of the signal demonstrated peculiarities of grain size effect in some way similar to that seen in the present work. New approaches like dynamic X-ray measurements that use a synchrotron radiation source [16] as well as protonography [17], both employing natural averaging along the ray direction, could provide important information if their resolution were improved.…”
Section: Discussionsupporting
confidence: 72%
“…Unfortunately, at low densities, fluctuations complicate the laser interferometry at the interface [12]. The method [15] using thick foils which provide averaging of the signal demonstrated peculiarities of grain size effect in some way similar to that seen in the present work. New approaches like dynamic X-ray measurements that use a synchrotron radiation source [16] as well as protonography [17], both employing natural averaging along the ray direction, could provide important information if their resolution were improved.…”
Section: Discussionsupporting
confidence: 72%
“…The designations of the profiles in Figures 2 and 3 correspond to the experiment numbers in Table 1. The obtained velocity profiles for CL-20 are qualitatively similar to those previously observed in pressed RDX, HMX and other explosives, e. g. [18,[28][29][30][31][32][33]. As an example, Figure 2 shows the dependence of velocity on time for PETN, obtained under the similar experimental conditions [30].…”
Section: Steady-state Detonation Of Cl-20supporting
confidence: 81%
“…Nevertheless, based on the obtained particle velocity profiles, it is concluded that this time is about 50 ns at the CL-20 initial density of 1.98 g/cm 3 . Similar values of reaction time are observed for many other pressed explosives [29,31,42], including CL-20based explosive containing 96 % CL-20, for which this time is equal to 48 ns [18]. In this respect, CL-20 does not exhibit any features that could be caused by high pressure at the CJ point.…”
Section: Steady-state Detonation Of Cl-20supporting
confidence: 76%
“…It is due to the fact that in 0.1 msec after the arrival of the shock wave at the foil-water interface, the decrease in the velocity related to the presence of a chemical spike in the explosive is replaced by its sharp increase due to the arrival of the compression wave rereflected from the explosive-foil interface. All details of the flow associated with circulation of waves in the foil can be analyzed in detail in the pressure-particle velocity plane (see [4]). In this case, it is important to note that in the experiment using a 400-μm thick foil, velocity oscillations disappear and the resulting dependence becomes smooth.…”
Section: Fefomentioning
confidence: 99%